ChemInform Abstract: A Facile Synthesis of (5‐Hydroxy‐4‐oxo‐4H‐pyran‐2‐yl)methyl Carboxylates and Their Antiviral Activity Against Hepatitis C Virus. Issue 39 (5th September 2013) - Shimo, Tetsuro; Taketsugu, Yuki; Goto, Takuya; Toyama, Masaaki; Yoshimura, Kohji; Baba, Masanori
Abstract Twelve oxopyranyl‐based compounds like (I) are synthesized in three steps from kojic acid in relatively good yields and investigated for their cytotoxicity and anti‐HCV activity in subgenomic HCV replicon cells.